Strukturoptimering av ett fäste i en jetmotor med varierande last Produktutveckling av ett fäste mellan kompressormellanhus och yttre fläktledskenor - Skoog, Julia; Åström , Anna (My University, 2026)
This bachelor thesis was carried out on behalf of GKN Aerospace and examines the possibility of moving an engine mount from the Intermediate Compressor Case (IMC) to the Fan Case Mount Ring (FCMR). Such a change creates a need for a new connection between the IMC and the Fan Exit Guide Vanes (FEGV) that can provide a functional load path while also meeting technical requirements regarding strength, weight and assembly. The purpose of the project was therefore to develop and evaluate different concepts for such a connection. The project followed a structured product development process with focus on problem definition, data collection, requirement specification, functional analysis, concept generation and concept evaluation. During the project, important requirements were identified, such as low weight, good strength, ease of assembly, compatibility with the existing design and manufacturability. Several concepts were developed and evaluated. The most promising concepts were then modelled in CAD and analysed with finite element method in ANSYS. The concepts were mainly compared based on stress levels in relation to the materials properties and weight. After the analyses, concept A3, a solution with support struts, was considered the most suitable alternative. The concept showed good structural performance, acceptable stress levels and competitive weight compared with the other concepts. The conclusion of the project is that there is good potential to create a functional connection between the IMC and FEGV. With further development, geometry optimisation and more detailed analyses, concept A3 could be an interesting alternative for future industrial use.